Budaya Membaca Mahasiswa Semester Akhir Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kupang - Ainurrofiq Ibrahim (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
This research aims to determine the reading culture among students in the final semester of the teaching and education faculty, at Muhammadiyah University of Kupang, and to determine the library's strategy for increasing reading interest among students in the final semester of the teaching and education faculty, Muhammadiyah University of Kupang. This study uses a qualitative method. The subjects in this research were final semester students of the teaching and education faculty, employees, and the head of the library. Collect data using observation, interviews, and documentation. Meanwhile, the data analysis process used is data reduction, data presentation and conclusions. The results of the research show that students' reading culture is improving, as seen from the number of reading sheets read, ranging from 10 to 40 pages per day and due to the need for information and knowledge which is used as a reference in preparing final assignments. Meanwhile, the library's strategy is to increase interest in reading, namely an adequate library, a book collection tailored to student needs and regular funds every year.